2015
DOI: 10.1007/s11284-015-1315-x
|View full text |Cite
|
Sign up to set email alerts
|

Pastoralist disturbance effects on Himalayan marmot foraging and vigilance activity

Abstract: Pastoralism is pervasive and has a long history across the rangelands of Trans-Himalaya. Disturbance associated with pastoralism can influence the behaviour of wild animals; hence, it is important to better understand its effects on wild animal behaviour. We compared the activity budget of the Himalayan marmot (Marmota himalayana) between areas experiencing both high and low levels of pastoralism, in the Upper Mustang region in Nepal. Scan sampling was used to collect diurnal activity budget data on adult marm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 86 publications
1
12
1
Order By: Relevance
“…Many authors have investigated the responses of breeding birds to human disturbance, such as the energy costs of earlier flight initiation and vigilance (e.g., González et al 2006, Poudel et al 2015, changes in habitat use (e.g., Lafferty 2001, Fernández-Juricic et al 2002, Markovchick-Nicholls et al 2008, Lowe et al 2014, reduced parental care (e.g., Burger 1994, Verhulst et al 2001, Bautista et al 2004, Yasué and Dearden 2006, and decreased reproductive success (Safina andBurger 1983, Bailly et al 2016). Behavioral responses to human disturbance vary among species (Blumstein et al 2005), with, e.g., group-living species more likely to suffer from injuries during panic behavior (Carney and Sydeman 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have investigated the responses of breeding birds to human disturbance, such as the energy costs of earlier flight initiation and vigilance (e.g., González et al 2006, Poudel et al 2015, changes in habitat use (e.g., Lafferty 2001, Fernández-Juricic et al 2002, Markovchick-Nicholls et al 2008, Lowe et al 2014, reduced parental care (e.g., Burger 1994, Verhulst et al 2001, Bautista et al 2004, Yasué and Dearden 2006, and decreased reproductive success (Safina andBurger 1983, Bailly et al 2016). Behavioral responses to human disturbance vary among species (Blumstein et al 2005), with, e.g., group-living species more likely to suffer from injuries during panic behavior (Carney and Sydeman 1999).…”
Section: Introductionmentioning
confidence: 99%
“…We found that as a residential species that have to share the same space with human, pairs of Himalayan marmots in Zoige wetland tended to dig more burrows relative to pairs in NH, resulting in shorter interburrow distances if they are suffered persistent but nonfatal disturbance from human activities (Bryant, 1996;Griffin et al, 2007) due to their high phenotypic plasticity (Huang et al, 1986;Poudel et al, 2015aPoudel et al, , 2015b. Besides, most breeding pairs in the region generally prefer to construct their reproductive burrows on mounds.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, some certain other residential species like some rodents (Harris & Munshi-South, 2017;Maher, 2009), primates (Marty et al, 2019), and some carnivores like some red fox populations (Jahren et al, 2020;Lambe, 2016) are better able to adapt and survive in human-dominated habitats and gain a higher population density relative to their rural congeners. To deal with different human influences suffered, animals have adopted multiple survival strategies such as adjusting time rhythm (Poudel et al, 2015a), allocating more time to vigilance (Griffin et al, 2007;Poudel et al, 2015b), or using habitats farther away from human activity (Macedo et al, 2018;Paudel & Kindlmann, 2012;Pita et al, 2020).…”
mentioning
confidence: 99%
See 2 more Smart Citations